Analisis Penerapan Strategi Digital Marketing dan Nilai Keberlanjutan pada Usaha Pangan Lokal - Vista Uli Sihombing; Futri Medwina Siregar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Current technological developments have driven significant changes in the marketing strategies of local food businesses while also opening up opportunities to integrate sustainability values into business activities. Digital marketing has become an important tool for micro, small, and medium-sized enterprises (MSMEs) in the local food sector to expand their market reach, increase competitiveness, and communicate product advantages amid growing consumer awareness of sustainability issues. This study aims to analyze the level of implementation of digital marketing strategies by local food businesses and identify the extent to which sustainability values are applied and communicated in the production and promotion of products. The study was conducted in Medan City, Binjai City, and Deli Serdang Regency using a descriptive quantitative approach through a survey method. Primary data was collected using questionnaires from 150 local food businesses that have utilized digital marketing. The results show that most businesses have adopted digital marketing through social media, especially Facebook and WhatsApp, but the use of online marketplaces and structured digital marketing strategies is still relatively low. In terms of sustainability, the majority of businesses have used environmentally friendly local raw materials, but the application of environmentally friendly packaging, certification ownership, and communication of sustainability values in promotions is still limited. These findings indicate that although the application of digital marketing in local food businesses is quite good at a basic level, strengthening digital marketing strategies and communication of sustainability values is still needed to support the long-term sustainability of the business.